ANALISA PENERAPAN PUTUSAN ULTRA PETITA OLEH MAHKAMAH KONSTITUSI DALAM PUTUSAN PERSELISIHAN HASIL PEMILIHAN UMUM - Putri, Ratu Syifa Junaedi; Farhan, Alif; Wasistha, Ariani Nurhanifah Putri (Jurnal Media Justitia Nusantara, 2023)
The Constitutional Court is a particular judicial state institutions that has a position as a judicial institution besides the Supreme Court. Their responsibilities and power are controlled in Article 24C paragraph (1) of the 1945 Constitution of the Republic of Indonesia, where one of them is determining disputes over the outcome of the presidential elections. Requests for these types of issues may only be submitted by election participants considering the rules and regulations provided in Law no. 24 of 2003. In giving a decision, the judge has the right to find his own law, including giving a decision that exceeds the application submitted by the applicant which is called a decisionultra small. This is intended to provide substantive justice to the applicants. The objective of doing  this research is to analyze whether the decisionultra smallcan be applied in the issue of disputes over election results. For this reason, , a normative research was conducted using a qualitative methodology so that the results provided are a comprehensive discussion. The outcomes from this research prove that the verdictultra smallcan be given to cases of disputed election results. Example of applicationultra small against the action of the Constitutional Court is the Constitutional Court Decision Number 41/PHPU.D-VI/2008 and the Constitutional Court Decision Number 57/PHPU.D-VI/2008.Keywords:ultra petita, verdict, election dispute